Project-Based Learning Evaluation trends in 21st Century Skills Development: bibliometrics and VoS Viewer: Tren Evaluasi Pembelajaran Berbasis Proyek dalam Pengembangan Keterampilan Abad ke-21: bibliometrik dan VoS Viewer - Alvira Pranata; Tri Syamsijulianto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate research trends related to Project-Based Learning (PjBL) in 21st-century skills development through a bibliometric approach. 21st-century skills, such as critical thinking, collaboration, communication, and creativity, are a major focus in modern education, and PjBL is seen as a relevant pedagogical approach to cultivating those skills. However, systematic mapping of research trends and scientific collaboration in this field is still limited. This study uses a bibliometric method by analyzing 174 articles indexed by Sinta and Scopus from 2015 to 2025, which contain keywords related to